2009
DOI: 10.1021/jm9015284
|View full text |Cite
|
Sign up to set email alerts
|

The Discodermolide Hairpin Structure Flows from Conformationally Stable Modular Motifs

Abstract: (+)-Discodermolide (DDM), a polyketide macrolide from marine sponge, is a potent microtubule assembly promoter. Reported solid-state, solution, and protein-bound DDM conformations reveal the unusual result that a common hairpin conformational motif exists in all three microenvironments. No other flexible microtubule binding agent exhibits such constancy of conformation. In the present study, we combine force-field conformational searches with NMR deconvolution in different solvents to compare DDM conformers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 69 publications
1
11
0
1
Order By: Relevance
“…This set back, along with the observation of synergistic activity with paclitaxel has contributed to a significant interest in preparing analogs of discodermolide with reduced toxicity [34]. Substantial research has also gone into defining the binding pose of discodermolide bound to purified tubulin and assembled microtubules [35-37]. The majority of these use molecular mechanics calculations and NMR methods to define structural features in discodermolide that interact with tubulin and to rationalize these with the known structure activity data [34].…”
Section: Tubulin Active Agents-leads For Development Of Clinically Usmentioning
confidence: 99%
“…This set back, along with the observation of synergistic activity with paclitaxel has contributed to a significant interest in preparing analogs of discodermolide with reduced toxicity [34]. Substantial research has also gone into defining the binding pose of discodermolide bound to purified tubulin and assembled microtubules [35-37]. The majority of these use molecular mechanics calculations and NMR methods to define structural features in discodermolide that interact with tubulin and to rationalize these with the known structure activity data [34].…”
Section: Tubulin Active Agents-leads For Development Of Clinically Usmentioning
confidence: 99%
“…Although NMR data in water has not been recorded, past studies have indicated that changes in solvent only entail a change in the distribution of already existing conformations without altering their essential form. 21,22 Such an identity-preserving shift in the populations of stevastelin conformers induced by other solvents would not be unanticipated. Relevant NMR data on stevastelins in water could make such an analysis computationally tractable.…”
Section: Conformations Of Stevastelin C3 Analogs 973mentioning
confidence: 99%
“…Thus, NAMFIS serves as a useful alternative to purely theoretical methods for investigating molecular conformations. Previously, NAMFIS has been successfully used to determine bioactive conformations in solution for medicinally important molecules such as taxol, 19 epothilones, 20 discodermolide, 21 laulimalide, 22 and geldanamycin 23 and has also been used in the study of helical peptides. 24 In some of these studies, the bioactive conformation has been located as a relatively minor component of the solution ensemble amounting to not more than a few percent, underscoring the difficulty in teasing out these minor conformations from time-averaged structural data.…”
Section: Introductionmentioning
confidence: 99%
“…Docking studies then identified two distinct docking poses, and one of them was identified as better accommodating the available SAR data. 11 …”
Section: Introductionmentioning
confidence: 99%